Potential Health Effects Associated with Dermal Exposure to Occupational Chemicals - Stacey E. Anderson; B. Jean Meade (SAGE Publishing, 2014)
There are a large number of workers in the United States, spanning a variety of occupational industries and sectors, who are potentially exposed to chemicals that can be absorbed through the skin. Occupational skin exposures can result in numerous diseases that can adversely affect an individual's health and capacity to perform at work. In general, there are three types of chemical-skin interactions of concern: direct skin effects, immune-mediated skin effects, and systemic effects. While hundreds of chemicals (metals, epoxy and acrylic resins, rubber additives, and chemical intermediates) present in virtually every industry have been identified to cause direct and immune-mediated effects such as contact dermatitis or urticaria, less is known about the number and types of chemicals contributing to systemic effects. In an attempt to raise awareness, skin notation assignments communicate the potential for dermal absorption; however, there is a need for standardization among agencies to communicate an accurate description of occupational hazards. Studies have suggested that exposure to complex mixtures, excessive hand washing, use of hand sanitizers, high frequency of wet work, and environmental or other factors may enhance penetration and stimulate other biological responses altering the outcomes of dermal chemical exposure. Understanding the hazards of dermal exposure is essential for the proper implementation of protective measures to ensure worker safety and health.